Types Of Corruption Education In Medan City - Hasbi, Hasbi (International Asia Of Law and Money Laundering, 2024)
Corruption crimes occur in North Sumatra precisely in the city of medan with various types of cases in various fields. The field of education is one of the fields used by corruptors to enrich themselves . The most dominant forms of corruption occur such as unauthorized levies on students and misuse of school operational assistance funds.the analysis uses Jack Bologne'S GONE theory to describe the characteristics of corruption in education. It is important to provide an understanding of the form and characteristics of the crime in order to determine the countermeasures properly. forms of corruption in the field of education in the city of medan. Modus operandi of the perpetrators it is very easy to commit corruption because lack of oversight on the part of local governments as well as the tendency of law enforcement who are reluctant to handle cases of corruption in the field of education although aware of the practice of illegal levies made by the school to its students. Of the various forms of corruption in the field of education is then done.